Role of Technical Institution in Development of Entrepreneurship - Asawa, R. R. (Journal of Engineering Education Transformations, 1990)
The present is a time of entrepreneurial ferment, where old and staid institutions suddenly have to become very limber, unless and until there is a major reform in the engineering curricula, it will not be possible for the student to stand to pressure of international competition in Technology in 21 st Century and solve the unemployment problem effectively.